Acoustic and long-term average spectrum measures to detect vocal aging in women - Da Silva, Paula Torres; Master, Suely [UNESP]; Andreoni, Solange; Pontes, Paulo; Ramos, Luiz R. (Elsevier, 2011)
Along the normal aging process, voice tends to become weak, breathy, and loses projection, which may interfere in the communication process. One reliable way to evaluate voice quality is through acoustical analysis using, for instance, the long-term average spectrum (LTAS). The aim of this study was to identify acoustic measures, particularly LTAS's, which characterize vocal aging in women without vocal complaints. For this purpose, 30 elderly and 30 young women were included in this study. All spoke standard Portuguese and none had a history of vocal and laryngeal alterations or respiratory diseases. On the basis of the reading task, in habitual and loud levels, the following parameters were assessed: the equivalent sound level (Leq), the speaking fundamental frequency (SFF) and, at the LTAS window, the difference between the levels of the regions of the first formant and fundamental frequency F0 (L 1 - L0), alpha ratio, and the amplitude levels obtained at equal intervals of 160 Hz, ranging from 0 to 8 kHz. There were significant differences between young and old voices for SFF and Leq in both levels. In the LTAS window, amplitude levels were higher for young voices, comprising all frequencies except those in the regions between 4.6-6.7 and 4.8-6.5 kHz, in habitual and loud levels, respectively. There were also significant differences regarding L1 - L0 and alpha ratio between groups, in both levels.The observed differences in LTAS's slopes, L 1 - L0 measures, and even Leq and SFF measures, may be attributed, to some extent, to lower subglottal pressure or a glottal setting providing a slower glottal closing speed for the elderly group. © 2011 The Voice Foundation.
Keywords: Acoustic analysis; Long-term average spectrum; Vocal aging; Voice quality